Curcubita moschata Seeds: Ancestral Flavor and Nutrition for Current Use - Elsa Julieta Salazar; María Eunice Cota (Biology and Life Sciences Forum)
The squash, C. moschata, is a type of pumpkin that grows easily in milpas—small, polyculture fields in Guatemala. Excavations carried out in pre-Columbian mounds in Uaxactún, Petén, indicate that squash has been cultivated and consumed for more than 5000 years. Today, both the pulp and the seed are still used as food; seeds are processed by hand and sold as toasted seed, or as toasted and ground seed with added salt, which is called pepita. The seed is used as a flavoring and thickening ingredient in sauces and pepita is used as an accompaniment to fresh fruit. This work aimed to provide updated information on the nutritional compositions of squash seeds and pepita in popular markets in the north, center, west, and southeast of Guatemala. The moisture content was determined in a convection oven at 60 °C, the ash by combustion in furnace at 450 °C, the protein by Kjeldahl method, fat by solvent extraction in the goldfish apparatus, and minerals by atomic absorption spectroscopy; and a UV/VIS colorimeter. The moisture content in seeds and pepita were 5.67% and 4.65%; ash 4% and 6.24%; protein 32.9% and 29.21%; lipids 32.07% and 30.22%, respectively. There was a higher content of macrominerals in pepita than in seeds, due to the salt addition. Comparing the nutritional results of the dry seed with those reported in the Food Composition Table for Central America, differences in protein and fat content are greater than 10%.